Implementasi Model Pembelajaran Berbasis Project (PjBL) pada Mata Kuliah Manajemen Pendidikan - Eva Nirtha; Ermelinda Agnes Gunu Pure; Faustina Ngali Mahuze; Serlina Boru Sinaga; Roberto W. Marpaung (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2025)
This study aimed to analyze the implementation of the project-based learning model (PjBL) in the Education Management course and identify its impact on student engagement, concept understanding, and critical thinking skills. The research approach used a qualitative descriptive method with data collection techniques used observation, in-depth interviews with lecturers and students, and analysis of project assignment documents. The results of the study show that the implementation of PjBL is able to increase active student participation, encourage collaboration in groups, and strengthen students' ability to integrate education management theory with real practice through the resulting project products. PjBL has been proven to increase student motivation and responsibility for the learning process. However, the study also found several obstacles such as variations in teamwork skills, time constraints, the need for intensive guidance from lecturers. However, this challenge does not reduce the effectiveness of PjBL, in fact it shows that the success of this model depends heavily on careful planning, consistent mentoring, and project design that is relevant to the needs of students. Overall, the implementation of PjBL in the Education Management course is considered effective and relevant to develop the professional competence of prospective teachers.